A Study On Capital Structure Of Domestic And Multinational Companies - KANAGARAJU, Dr. P.; SATHYA, S. (The journal of contemporary issues in business and government, 2021)
Capital structure is the composition of debt and equity securities that are used to finance a company’s assets. The choice of debt and equity is an important decision for the corporate sector because an optimal choice of financing decision increases the value of the firm. The Multinational corporations (MNC) has benefits over the Domestic companies (DC) with regard to debt raising capacity, wider options for raising capital, greater options to generate profits, diversification benefits, economies of scale, etc. This paper investigates the determinants of capital structure of domestic and multinational companies during the period 2010 to 2020. The study concluded that the significant capital structure determinants are Size, Return on Sales, Return on Assets and Profit.